Performance Pay and Applicant Screening - Uwe Jirjahn; Jens Mohrenweiser (Global Labor Organization (GLO), 2017)
Using German establishment data, we show that the relationship between intensity of performance pay and intensity of applicant screening depends on the nature of production. In establishments with increased multitasking, performance pay is positively associated with applicant screening. By contrast, in establishments without increased multitasking, performance pay is negatively associated with applicant screening. The findings fit the hypothesis that performance pay induces a positive self-sorting of employees if jobs are less multifaceted. In this case, employers with a high intensity of performance pay do not need intensive applicant screening to ensure a high quality of matches between workers and jobs. However, if jobs are more multifaceted, performance pay can entail problems of adverse self-sorting. In order to mitigate or overcome these problems, employers making intensive use of performance pay also screen applicants more intensively.
Keywords: J33; J60; M51; M52; 330; Performance pay; multitasking; self-sorting; applicant screening; non-managerial employees; managerial employees